Analisis Ekonomi Terhadap Produk Aki Bekas Merek GS - Utomo, Aldy Prasetyo; Arafi, Arafi; Hidayat, Syamsul (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
GS (Gelora Sinar) brand batteries are one of the superior products in the vehicle battery industry in Indonesia. Known for its high quality and durability, GS batteries have become the main choice for motor vehicle users. This product is designed with the latest technology that supports optimal performance and energy efficiency. In addition, GS is committed to sustainable practices by implementing a used battery recycling program, which aims to reduce the environmental impact of hazardous waste. In facing intense competition in the market, GS is also active in conducting outreach and education to consumers regarding the importance of battery maintenance and waste management. With a strong reputation and continuous innovation, GS batteries continue to adapt to market needs, making it one of the leading brands in the battery industry in Indonesia.